Optimalisasi Pemanfaatan Limbah Kulit Nanas sebagai Produk Pangan Fungsional melalui Program Pengabdian kepada Masyarakat di Desa Mandor, Kabupaten Landak: Optimization of Pineapple Peel Waste Utilization as a Functional Food Product through a Community Service Program in Mandor Village, Landak Regency - Mariani, Yeni; Yusro, Fathul; Yanti, Hikma; Setyawati, Dina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community education activity aimed to inform residents of Mandor Village, Landak Regency, about the use of pineapple (Ananas comosus L. Merr.) peel as a raw material for producing probiotic beverages. Pineapple peel, which has long been regarded as agricultural waste, contains nutrients such as carbohydrates, vitamins, minerals, and bromelain that can serve as a natural substrate for fermentation. The activity implementation consisted of three stages: preparation, implementation, and evaluation. The preparation stage involved collecting scientific information and creating samples of fermented products. The implementation stage included a lecture on functional foods and probiotics, followed by a demonstration of the production of a probiotic beverage using pineapple peel. The evaluation was conducted by distributing questionnaires before and after the activity to assess improvements in participants’ knowledge and interest. The results showed that participants demonstrated high enthusiasm (93.75%) in understanding the concepts of functional food and in developing practical skills for producing probiotic drinks from pineapple peel. This activity successfully raised community awareness about transforming agricultural waste into value-added products while fostering the independence of Mandor Village residents in developing local functional food-based enterprises.